E-Wom Yang Dirasakan Dalam Bentuk Pengaruh Visual Niat Pembelian Online Di Media Sosial - Avantika Raisha; Sri Vandayuli Riorini; Amanda Putri Bachtiar; Kelvina Clara Adelia (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
The rapid growth of visually oriented social media has significantly transformed the way consumers seek information and shape their purchasing decisions through electronic word of mouth (eWOM). This study aims to analyze the influence of visual eWOM characteristics on online purchase intention using the Stimulus–Organism–Response (SOR) framework. Specifically, it examines the roles of visual information quality and information credibility in affecting information usefulness and information adoption, which subsequently influence consumers’ purchase intentions. This study employs a quantitative approach with a cross-sectional research design. Data were collected through an online questionnaire distributed to 208 active social media users in Indonesia who have experience purchasing products based on visual eWOM content. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine the relationships among the constructs in the proposed model.The results indicate that the quality of visual eWOM information has a positive and significant effect on both information usefulness and information adoption. These variables also act as mediators that strengthen their influence on online purchase intention. In contrast, information credibility does not show a significant effect on either information usefulness or information adoption in this context. These findings suggest that consumers tend to prioritize the quality of visual presentation and the ease of understanding information over the perceived credibility of the source.In conclusion, within visually driven social media environments, content quality plays a crucial role in shaping consumer purchase decisions. The findings provide practical implications for businesses to focus on creating visually appealing and informative content to enhance the effectiveness of digital marketing strategies.